2020
DOI: 10.1002/cssc.202000559
|View full text |Cite
|
Sign up to set email alerts
|

Scalable Synthesis of Microsized, Nanocrystalline Zn0.9Fe0.1O‐C Secondary Particles and Their Use in Zn0.9Fe0.1O‐C/LiNi0.5Mn1.5O4 Lithium‐Ion Full Cells

Abstract: Conversion/alloying materials (CAMs) are a potential alternative to graphite as Li‐ion anodes, especially for high‐power performance. The so far most investigated CAM is carbon‐coated Zn 0.9 Fe 0.1 O, which provides very high specific capacity of more than 900 mAh g −1 and good rate capability. Especially for the latter the optimal particle size is in the nanometer regime. However, this leads to limited electrode packing densities and safety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 51 publications
1
16
0
Order By: Relevance
“…First, it has been shown that cycling Zn 0.9 Fe 0.1 O-C in a wide voltage window (i.e., between 0.01 and 3.0 V) leads to an unstable solid electrolyte interphase and, second, leads to a lower energy efficiency and density. [31,32,35] Consequently, such limitation to a narrower voltage range is beneficial for lithium-ion cells using such anodes if suitable prelithiation techniques are scaled up to the industrial level. [43] The high cycling stability of the gravure-printed electrodes may be explained by the high homogeneity of the final gravure-printed electrodes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…First, it has been shown that cycling Zn 0.9 Fe 0.1 O-C in a wide voltage window (i.e., between 0.01 and 3.0 V) leads to an unstable solid electrolyte interphase and, second, leads to a lower energy efficiency and density. [31,32,35] Consequently, such limitation to a narrower voltage range is beneficial for lithium-ion cells using such anodes if suitable prelithiation techniques are scaled up to the industrial level. [43] The high cycling stability of the gravure-printed electrodes may be explained by the high homogeneity of the final gravure-printed electrodes.…”
Section: Resultsmentioning
confidence: 99%
“…Zn 0.9 Fe 0.1 O–C was prepared via a recently reported scalable process including spray drying. [ 31 ] In brief, an aqueous solution of zinc(II) acetate dihydrate (Alfa Aesar) and iron(II) d ‐gluconate dihydrate (Aldrich) was spray dried (with a GEA Niro Mobile Minor spray dryer) and the resulting powder was calcined at 450 °C for 3 h (VMK‐1400, Linn High Therm) and subsequently ball milled (Pulverisette 5, Fritsch). The resulting powder of Zn 0.9 Fe 0.1 O nanoparticles was dispersed in an aqueous solution of β ‐lactose, spray dried, and then thermally treated at 500 °C for 4 h under an argon atmosphere (MK‐135‐S, Linn High Therm).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[19] These materials are commonly based on the oxide or sulfide of an alloying element such as zinc, germanium, or tin, which have been intensively studied in different compositions and morphologies due to their high capacities and low working voltage, [13,20,21] and contain additionally a small amount of one or more transition metals that confines the aggregation of the alloying element and ensures a sufficient electronic conductivity within the initial primary particles to enable the reversible formation of Li 2 O. [19,[22][23][24][25][26][27][28][29][30][31][32][33][34][35] As already shown in a previous study, the incorporation of the Mn dopant into the SnO 2 structure allows for stable cycling and high reversible capacities with good rate performance, precisely, 1276 mAh g −1 at 20 mA g −1 and 651 mAh g −1 at 2 A g −1 , for instance. [34] A first estimation of the achievable specific energy revealed a potential improvement, e.g., for LIBs comprising Sn 0.9 Mn 0.1 O 2 (SMO) as the active material for the negative electrode and LNMO for the positive electrode with about 480 Wh kg −1 compared to 454 Wh kg −1 for a LIB containing graphite and LNMO (based on the mass of the active materials only, experimental data for the anode and theoretical data for the cathode).…”
Section: Introductionmentioning
confidence: 99%
“…[8] Among the most investigated members of this class are transition metal (TM)-doped zinc oxides (with TM ¼ Fe, [9][10][11][12][13][14] Co, [15,16] or Mn [17,18] ), providing a theoretical specific capacity of almost 1000 mAh g À1 and good cycling performance, thus clearly outperforming pure ZnO. [9,19] It has been proposed that the "intimacy of mixing" the different metals plays a decisive role in the electrochemical performance. [20] In fact, doping, e.g., ZnO with TMs is essentially equivalent to the mixing of different elements at the atomic level.…”
Section: Introductionmentioning
confidence: 99%